2015
DOI: 10.1530/eje-14-0880
|View full text |Cite
|
Sign up to set email alerts
|

Circulating acylghrelin levels are suppressed by insulin and increase in response to hypoglycemia in healthy adult volunteers

Abstract: Objective: Ghrelin has glucoregulatory and orexigenic actions, but its role in acute hypoglycemia remains uncertain. We aimed to investigate circulating levels of acylghrelin (AG) and unacylated ghrelin (UAG) in response to hyperinsulinemia and to hypoglycemia. Design: A randomized, single-blind, placebo-controlled crossover study including 3 study days was performed at a university hospital clinical research center. Methods: Nine healthy men completed 3 study days: i) saline control (CTR), ii) hyperinsulinemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Basal plasma ghrelin in STZ-treated WT mice ( Figure 2D ) was significantly higher than levels usually observed in non-STZ-treated WT mice, as expected ( 34 41 ). Also as expected from other studies that examined the effects of insulin on plasma ghrelin or ghrelin secretion ( 41 , 53 57 ), plasma ghrelin fell (~79%) in STZ-treated WT mice over the course of the clamp ( Figure 2D ). Nonetheless, plasma ghrelin remained much higher than the essentially undetectable level in ghrelin-KO littermates ( Figure 2D ).…”
Section: Resultssupporting
confidence: 85%
“…Basal plasma ghrelin in STZ-treated WT mice ( Figure 2D ) was significantly higher than levels usually observed in non-STZ-treated WT mice, as expected ( 34 41 ). Also as expected from other studies that examined the effects of insulin on plasma ghrelin or ghrelin secretion ( 41 , 53 57 ), plasma ghrelin fell (~79%) in STZ-treated WT mice over the course of the clamp ( Figure 2D ). Nonetheless, plasma ghrelin remained much higher than the essentially undetectable level in ghrelin-KO littermates ( Figure 2D ).…”
Section: Resultssupporting
confidence: 85%
“…These results suggest that glargine's suppression of ghrelin levels might attenuate the improvement in vascular endothelial function resulting from glycaemic control. A previous study showed that insulin injection suppressed acyl ghrelin levels, even in healthy euglycaemic adults [30], suggesting that insulin may depress ghrelin excretion. In the present study, acyl ghrelin level was significantly decreased by glargine treatment but not detemir treatment.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study in healthy volunteers demonstrated that acylated ghrelin levels are low under hyperinsulinemia conditions, followed by a subsequent increase in plasma ghrelin levels. 89 The authors even suggested that this fluctuation in ghrelin levels in response to acute hyperinsulemia would contribute to a rise of hunger sensation and therefore of food intake which are indeed observed after episodes of hypoglycemia. 89 Studies in animal models have demonstrated that ghrelin increases hepatic glucose production 62 by activating the gluconeogenic processes and/or via GH (which in its turn causes an increased hepatic glucose production).…”
Section: Ghrelin and Intermediary Metabolismsmentioning
confidence: 99%